ANALYSIS OF THE EFFECT OF ONLINE SHOPPING VALUE, EFFECTIVENESS OF INFORMATION CONTENT ON PURCHASE INTENTION WITH WEB SATISFACTION AS MEDIATION ON MILLENNIALS IN BATAM CITY - Lily Purwianti; Felby Jeslyn (Journal of Business Studies and Management Review, 2021)
The development of e-commerce with the C2C category is very fast and is dominated by the millennial generation. The millennial generation is a generation that was born in modern and technologically advanced conditions. Therefore, it is necessary to research. This investigation was conducted to determine whether online buying values ​​also the effectiveness of information content affect Web Satisfaction and will affect millennial buying intentions in Batam city. Data samples in this study were carried out by distributing questionnaires to 350 data and treated by SmartPLS. The outcomes of this investigation state that hedonic shopping value, utilitarian shopping value, the effectiveness of information content affect purchase intention, also Satisfaction as a mediation between hedonic shopping value, utilitarian shopping value, the effectiveness of information content, also purchase intention